2008
DOI: 10.4142/jvs.2008.9.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of a 3rd GnRH injection administered six days after the 2nd GnRH injection of Ovsynch on the reproductive performance of Japanese black cows

Abstract: This study was designed to evaluate the reproductive performance of Japanese black cows following the 3rd injection of gonadotropin releasing hormone (GnRH) analogue administered concurrently with Ovsynch-based treatment on day 6 (day 1 = the day of ovulation). In Experiment 1, 12 cows were allocated into three groups: a control group that was subjected to Ovsynch treatment and then injected with a placebo on day 6; group 1 (Ovsynch + GnRH), which was subjected to Ovsynch treatment and was injected with GnRH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(35 reference statements)
0
1
1
Order By: Relevance
“…These results were in agreement with the previous reported in repeat breeder cows [ 10 , 20 ]. Present findings were lower than those recorded by others [ 21 , 22 ]. Studies revealed that the initiation of Ovsynch treatment on different days of estrous cycle influenced its effectiveness [ 23 ].…”
Section: Resultscontrasting
confidence: 95%
“…These results were in agreement with the previous reported in repeat breeder cows [ 10 , 20 ]. Present findings were lower than those recorded by others [ 21 , 22 ]. Studies revealed that the initiation of Ovsynch treatment on different days of estrous cycle influenced its effectiveness [ 23 ].…”
Section: Resultscontrasting
confidence: 95%
“…One of the hallmarks of most TAI is that they induce a synchronized ovulation of a dominant follicle. Whereas ovulation of a smaller follicle may be positive for oocyte quality, it would result in production of a smaller corpus luteum (CL) that may produce lower progesterone (P4) concentrations than are optimal for fertility (Vasconcelos et al, 2001;Perry et al, 2005;Gaja et al, 2008) This problem is further exaggerated due to the high metabolism of P4 that is characteristic of high-producing dairy cows (Sangsritavong et al, 2002;Wiltbank et al, 2006). Progesterone is essential for pregnancy maintenance, playing a decisive role in stimulating production of a large range of endometrial compounds, growth factors, immunosuppressive agents, enzymes, ions, and steroids (Geisert et al, 1992;Hugentobler et al, 2010;Forde et al, 2011).…”
Section: Introductionmentioning
confidence: 99%